1999
DOI: 10.1016/s0893-133x(98)00052-9
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in the Inhibition of Mouse In Vivo [3H]Ro 15-1788 Binding Reflect Selectivity for α1 versus α2 and α3 Subunit-Containing GABAA Receptors

Abstract: The benzodiazepines flunitrazepam, diazepam, and Ro 15-1788

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 25 publications
1
44
0
1
Order By: Relevance
“…Among parents and controls, age had no relation to binding. DISCUSSION We found that patients with SSADH deficiency have reduced benzodiazepine receptor binding measured with 11 C-FMZ-PET. Parents, clinically unaffected, showed no binding reduction.…”
Section: Figure 2 [11c]-flumazenil Pet Scans In An Affected Subject (mentioning
confidence: 61%
See 2 more Smart Citations
“…Among parents and controls, age had no relation to binding. DISCUSSION We found that patients with SSADH deficiency have reduced benzodiazepine receptor binding measured with 11 C-FMZ-PET. Parents, clinically unaffected, showed no binding reduction.…”
Section: Figure 2 [11c]-flumazenil Pet Scans In An Affected Subject (mentioning
confidence: 61%
“…There were statistically significant differences in 11 C FMZ binding among patients, parents, and controls in all ROIs except midbrain; in the globus pallidus, a trend toward significance was found (table 2 and figure 2). Since no significant left-right difference in cortical BP ND were found, left and right ROIs were averaged.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The in vivo receptor binding of compounds A, B and diazepam was measured according to previously published methods [15]. In brief, animals were dosed orally, typically as suspensions in 0.5% aqueous Methocel (A4C) (The Dow Chemical Company, Midland, USA), with the compound of interest.…”
Section: In Vivo Binding Studiesmentioning
confidence: 99%
“…with [ 3 H]Ro 15-1788 (diluted to 10 mCi/ml in isotonic saline and administered as 5 ml/g to mice and 1 ml/g to rats). The 3 min interval between administration of [ 3 H]Ro 15-1788 and killing the animal was chosen since it has previously been shown that this results in maximum in vivo binding [15]. The animals were culled by stunning and decapitation and trunk blood was collected into heparinised tubes.…”
Section: In Vivo Binding Studiesmentioning
confidence: 99%